Respostas
respondido por:
1
(1, 2)
y = ax + b
2 = a.1 + b
a + b = 2 (-1)
-a - b = -2
(3, 8)
y = ax + b
8 = a.3 + b
3a + b = 8
-a - b = -2
3a + b = 8
2a = 6
a = 6/2
a = 3
3a + b = 8
3.3 + b = 8
9 + b = 8
b = 8 - 9
b = -1
a = 3 e b = -1
y = ax + b
y = 3x - 1
F(4) = 3.4 - 1
F(4) = 12 - 1
F(4) = 11
y = ax + b
2 = a.1 + b
a + b = 2 (-1)
-a - b = -2
(3, 8)
y = ax + b
8 = a.3 + b
3a + b = 8
-a - b = -2
3a + b = 8
2a = 6
a = 6/2
a = 3
3a + b = 8
3.3 + b = 8
9 + b = 8
b = 8 - 9
b = -1
a = 3 e b = -1
y = ax + b
y = 3x - 1
F(4) = 3.4 - 1
F(4) = 12 - 1
F(4) = 11
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás